PERSEPSI MASYARAKAT DALAM PENGELOLAAN DANA BADAN USAHA MILIK DESA (BUMDES) JAYA BERSAMA DESA KOTO TINGGI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Aulia, Nadia Rezki; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
BUMDes is a business institution villages located in the village and managed by the community and village government in an effort to strengthen the economy of the village and formed according the needs and potential of the village.  BUMDes be a form of community empowerment from the government in the form of  the       autonomy of the village, where the village is expected to manage resources                independently and can improve the welfare for the people of the villagec with the support of funds from government assistance and programs offered to its                   members. The perception of the community is defined in this study as the process of individuals interpret the or give the meaning of which is associated with                  various aspects especially on the factors that influence it, namely education,              employment, income, and experience are in line with the levels of perception of the respondents.The purpose of this study was to determine the public perception of the programs offered as well as the fund management of BUMDes and  find out what factors that affect the perception of the community. The teory used in this  research is the the theory of perception.This research is a quantitative research with descriptive type.Population an sample in this research was taken from the number of members who join the BUMDes programe as much as 463 members. Sampling Technique used in this research is random sampling. Data collection is done by field observations and questionnaires. Analysis doing by means of descriptive statistics to describe the data obtained. The results of this study concluded that as much as (57,3%) of the respondents have the perception is not good, then as much as a (41,5%) had good perception and (1,2) to rate bad.  Keywords: Community Perception, BUMDes, Fund Management